Synaptic spinules are reliable indicators of excitatory presynaptic bouton size and strength and are ubiquitous components of excitatory synapses in CA1 hippocampus - Gore, Ashley; Yurina, Amaliya; Yukevich-Mussomeli, Anastasia; Nahmani, Marc (Frontiers in Synaptic Neuroscience, 2022)
Synaptic spinules are thin, finger-like projections from one neuron that become embedded within the presynaptic or postsynaptic compartments of another neuron. While spinules are conserved features of synapses across the animal kingdom, their specific function(s) remain unknown. Recent focused ion beam scanning electron microscopy (FIB-SEM) image volume analyses have demonstrated that spinules are embedded within ~25% of excitatory boutons in primary visual cortex, yet the diversity of spinule sizes, origins, and ultrastructural relationships to their boutons remained unclear. To begin to uncover the function of synaptic spinules, we sought to determine the abundance, origins, and 3D ultrastructure of spinules within excitatory presynaptic spinule-bearing boutons (SBBs) in mammalian CA1 hippocampus and compare them with presynaptic boutons bereft of spinules (non-SBBs). Accordingly, we performed a comprehensive 3D analysis of every excitatory presynaptic bouton, their embedded spinules, and postsynaptic densities, within a 5 nm isotropic FIB-SEM image volume from CA1 hippocampus of an adult male rat. Surprisingly, we found that ~74% of excitatory presynaptic boutons in this volume contained at least one spinule, suggesting they are fundamental components of excitatory synapses in CA1. In addition, we found that SBBs are 2.5-times larger and have 60% larger PSDs than non-SBBs. Moreover, synaptic spinules within SBBs are clearly differentiated into two groups: small clathrin-coated spinules, and 29-times larger spinules without clathrin. Together, these findings suggest that the presence of a spinule is a marker for stronger and more stable presynaptic boutons in CA1, and that synaptic spinules serve at least two separable and distinct functions.